2008
DOI: 10.1007/s11666-008-9285-y
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Sprayed Coatings of High-Purity Ceramics for Semiconductor and Flat-Panel-Display Production Equipment

Abstract: High-purity oxide ceramic powders of alumina (Al 2 O 3 ) and yttria (Y 2 O 3 ) have been developed to apply to semiconductor and flat-panel-display (FPD) production equipment. The ceramic coatings on the inside chamber wall of the equipment are required to have high erosion resistance against CFx plasma in dry etching process for microfabrications of the devices. It is found that the yttria coating formed from agglomerated-and-sintered powder consisting of large primary particles has smoother eroded surface wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 12 publications
(7 reference statements)
0
19
0
Order By: Relevance
“…Generally, reactive ion etching technology is a kind of ion assisting plasma etching technology, which combine with the chemical etching and physical etching by radicals and ion sputtering, respectively. 9 The etching rate of reactive ion etching technology is more than 10 times comparing to only chemical etching or physical etching at the condition of silicon wafer as the etching substrate. In the plasma etching, CF 4 serves as both chemical and physical etching agent, and reacts with the protective coating to form fluorocarbon film.…”
Section: Discussion On Plasma Etching Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, reactive ion etching technology is a kind of ion assisting plasma etching technology, which combine with the chemical etching and physical etching by radicals and ion sputtering, respectively. 9 The etching rate of reactive ion etching technology is more than 10 times comparing to only chemical etching or physical etching at the condition of silicon wafer as the etching substrate. In the plasma etching, CF 4 serves as both chemical and physical etching agent, and reacts with the protective coating to form fluorocarbon film.…”
Section: Discussion On Plasma Etching Mechanismmentioning
confidence: 99%
“…generates a larger amount of particle pollution in the etching chamber, resulting in the plasma gas reacting with aluminum substrate. 4,5 Recent systematic studies by Qin et al 6 and Kitamura et al [7][8][9] have revealed that sintered Y 3 Al 5 O 12 (YAG) bulk and Y 2 O 3 coating reveal the higher anti-plasma erosion resistance properties as compared with the traditional alumite film. However, it is difficult to process the sintered ceramic bulk into irregular profile structure in order to fit into the etching chamber.…”
mentioning
confidence: 99%
“…Alumina coatings are also used for their dielectric strength, suitable for insulating coatings extensively used in ozonizers [147]. Kitamura et al [148] have shown that coating density strongly affects dielectric strength for both Al 2 O 3 and Y 2 O 3 coatings, while the influence of purity is found to be much less important in their study. Toma et al [149] have used APS and HVOF processes to prepare alumina (Al 2 O 3 ) and magnesium spinel (MgAl 2 O 4 ) coatings designed for insulating applications.…”
Section: Aluminamentioning
confidence: 99%
“…Recent systematic studies by Kitamura et al have revealed that plasma-sprayed Y 2 O 3 coatings have higher plasma erosion resistance than Al 2 O 3 coatings as well as sintered bulk Al 2 O 3 against CF 4 -containing plasma at the actual conditions in semiconductor fabrication processes (Ref [6][7][8]. The studies have also found that sintered bulk Y 2 O 3 is still superior to plasma-sprayed coatings in terms of the plasma erosion resistance and retention of smoother eroded surface.…”
Section: Introductionmentioning
confidence: 99%
“…The studies have also found that sintered bulk Y 2 O 3 is still superior to plasma-sprayed coatings in terms of the plasma erosion resistance and retention of smoother eroded surface. Although the previous studies have clarified that the use of agglomerated-and-sintered Y 2 O 3 powder consisting of large primary particles of about 5 lm is effective for producing high anti-plasma erosion resistance retaining smooth surface, which may help prevent generation of large-sized particles, the surface roughness is still higher than that of the bulk ( Ref 7,8). The inferiority of the Y 2 O 3 coating of erosion resistance with roughness of the eroded surface has shown that further improvement is still required for plasma spray coating.…”
Section: Introductionmentioning
confidence: 99%